2019
DOI: 10.4018/ijpada.2019010104
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Digital Divide in Africa and Policy Implications

Abstract: This article investigates the reasons most African households are not using the internet and discusses the policy implications for bridging the digital divide. The International Telecommunication Union (ITU) reports that at the end of 2014, only 7 percent of households in LDCs, most of whom are in Africa, had Internet access. This study analyses data from the ITU database and other sources to identify the determinants of the digital divide in Africa. Results show that peculiar challenges such as affordability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Following the literature (Aikins, 2019;Forman, 2005;Hilbert, 2011;Oliveira & Martins, 2011), we accounted for the influence of firm-specific factors by including: size of firm, level of education of the workforce and type of ownership of the firm. We also included the following as proxies for the business environment and effectiveness of state institutions: quality assurance certification, geographical location of the firm, the firm holds the perception that labour regulations are an obstacle, access to electricity and the sector in which the firm operates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the literature (Aikins, 2019;Forman, 2005;Hilbert, 2011;Oliveira & Martins, 2011), we accounted for the influence of firm-specific factors by including: size of firm, level of education of the workforce and type of ownership of the firm. We also included the following as proxies for the business environment and effectiveness of state institutions: quality assurance certification, geographical location of the firm, the firm holds the perception that labour regulations are an obstacle, access to electricity and the sector in which the firm operates.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies identified limited access to physical infrastructure, illiteracy, social and cultural limitations, a lack of finance (affordability), lack of decision-making ability and segregation in employment as some of the barriers to women's adoption of digital technologies in Africa (Aikins, 2019;Ikolo, 2013). The importance of digital technologies for manufacturing, skills development, research and development, integration and intra-African trade, investment and tourism requires that policymakers pay particular attention to these sociocultural, economic and institutional factors that contribute to the gender-based digital divide at firm level on the African continent (African Union Commission, 2015).…”
Section: Estimates Of Digital Technology Adoption and Utilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of ICT can be harnessed almost in every sphere of socio-economic development such as education, health, employment, environment etc. In fact, the ICT is considered as the means of implementation of the various sustainable development goals (SDGs) (Aikins, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the least-developed countries, the lack of physical access (insufficient network coverage) and material access are the primary factors that create the digital divide. The challenges of affordability and the lack of digital skills in these countries also contribute to the digital divide (Aikins, 2019). Nevertheless, while a common opinion is that the digital divide is entirely solved when a country's Internet connection rate reaches saturation, recent works proved that the digital divide still exists in developed and technologically advanced countries where the network coverage is high (e.g., van Deursen & van Dijk, 2019).…”
Section: Disabled People and The Digital Dividementioning
confidence: 99%